2021
DOI: 10.1016/j.ijcha.2021.100842
|View full text |Cite
|
Sign up to set email alerts
|

Increased fibroblast accumulation in the equine heart following persistent atrial fibrillation

Abstract: Highlights Persistent atrial fibrillation is associated with increased fibroblast accumulation. Six weeks of persistent AF is not associated with structural remodeling. Fibroblasts are potentially contributing to alteration in atrial electrophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Tissue simulations showed that not only could the myofibroblast infiltration affect the arrhythmia vulnerability [ 73 , 74 ], but also the fibrosis pattern can play a role in the initiation and maintenance of reentrant activity [ 46 , 47 , 54 , 75 ]. Sridhar et al [ 76 ] have shown the role that fibroblast infiltration plays regarding the onset of arrhythmia due to the increase of anisotropy in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue simulations showed that not only could the myofibroblast infiltration affect the arrhythmia vulnerability [ 73 , 74 ], but also the fibrosis pattern can play a role in the initiation and maintenance of reentrant activity [ 46 , 47 , 54 , 75 ]. Sridhar et al [ 76 ] have shown the role that fibroblast infiltration plays regarding the onset of arrhythmia due to the increase of anisotropy in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether the same mechanisms exist in horses. However, as myofibroblasts are relatively common in equine atria, these cells are indeed of great interest and should be investigated more closely [41].…”
Section: Triggersmentioning
confidence: 99%
“…Structural changes, such as cellular hypertrophy, cellular dedifferentiation to a precursor and interstitial fibrosis have been reported in horses with persistent AF [5,10,51,52]. Studies investigating structural changes in response to AF found an increased number of atrial fibroblasts after 6 weeks of induced AF [41] and increased atrial fibrosis after 2 months of induced AF [10].Two major inflammatory drivers involved in fibrosis formation are angiotensin II and transforming growth factor β1 (TGF-β1). These factors are heavily involved in fibrogenesis, including the transformation of fibroblasts into collagen-producing myofibroblasts, and increased tissue levels have been found in the right atrium of patients with pAF.…”
Section: Atrial Remodelingmentioning
confidence: 99%
“…The histology of the consecutive sections of the AV node confirmed the presence of a cartilaginous structure at the base of the aortic leaflet in conjunction with the AV node and the penetrating bundle, also known as the His bundle ( Figure 4 ). An automatic quantification method of the amount of collagen [ 17 ] revealed no obvious differences in the amount of collagen, with 83% collagen in the case horse and a mean of 82 ± 17% in the control horses. The major difference was the location of the AV node in conjunction with the cartilage.…”
Section: Case Presentationmentioning
confidence: 99%